Yemen Early Childhood Development : SABER Country Report 2013 - World Bank (Washington, DC, 2014)
This report presents an analysis of the Early Childhood Development (ECD) programs and policies that affect young children in Yemen. This report is part of a series of reports prepared by the World Bank using the SABER-ECD framework and includes analysis of early learning, health, nutrition, and social and child protection policies and interventions in Yemen, along with regional and international comparisons. The SABER-ECD initiative is designed to enable ECD policymakers and development partners identify opportunities for further development of effective ECD systems. The SABER-ECD classification system does not rank countries according to any overall scoring; rather, it is intended to share information on how different ECD systems address the same policy challenges. This country report presents a framework to compare Yemen s ECD system with other countries in the region and internationally. Each of the nine policy levers are examined in detail and some policy options to strengthen ECD are offered. Yemen s National Strategy for Early Childhood shows a commitment to improving services for young children in the country. The challenge to address malnutrition, poor access to healthcare, low preschool enrollment, and other barriers to children s healthy development will be implementation. As the country moves through political transition, promoting early childhood development should be an important part of Yemen s progression to a civic state that serves all of its citizens. Investing in its youngest citizens is crucial to the country s future success. Table 14 offers policy recommendations and options that the government could consider to strengthen ECD.